Employment by choice and necessity among Canadian-born and immigrant seniors - René Morissette; Feng Hou (Economic and Social Reports)
Many seniors work past their mid-60s for various reasons. Some find it necessary to keep working because of inadequate retirement savings, mortgage payments, unforeseen expenses, or the responsibility to support children and other family members in Canada or abroad. Others choose to work to provide a sense of personal fulfillment, stay active and remain engaged. This article uses data from the Labour Force Survey (LFS) and examines the degree to which Canadian-born and immigrant seniors aged 65 to 74 worked by choice or necessity in 2022.